The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.21203/rs.3.rs-27194/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the Efficacy of Using Hypertonic Saline for Nebulizing Treatment in Children with Bronchiolitis: a Meta-Analysis of Randomized Controlled Trials

Abstract: Introduction: Acute bronchiolitis is the most common lower respiratory infection in children. It is particularly prone to dyspnea among children under two years old. Inhaled hypertonic saline (HS) has recently been shown to be a favorable therapy, because of its facility to draw fluid from the submucosa and adventitial spaces, decreasing airway edema. The aim of this systematic review and meta-analysis was to evaluate the efficacy and safety of HS in the implementation of vapor treatment among children with br… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The findings of the present study are partly consistent with those of previous studies. [54][55][56][57] In this study, the meta-analysis results showed significant differences between the 2 management strategies in terms of LOS reduction, ROH decrease, CSS improvement, and RDAI enhancement. This indicates that the efficacy of 3% NHS is better than that of 0.9% NS in the treatment of infants with AB.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…The findings of the present study are partly consistent with those of previous studies. [54][55][56][57] In this study, the meta-analysis results showed significant differences between the 2 management strategies in terms of LOS reduction, ROH decrease, CSS improvement, and RDAI enhancement. This indicates that the efficacy of 3% NHS is better than that of 0.9% NS in the treatment of infants with AB.…”
Section: Discussionmentioning
confidence: 53%
“…However, their findings are inconsistent. [48,[54][55][56][57] In addition, 2 high-quality RCTs [29,41] were published after the most recent review. [54] Based on a previous study, this study updated the findings and provided the latest evidence for 3% NHS in infants with AB.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HSS has also been extensively evaluated in acute bronchiolitis 7 . Although some publications did not find relevant efficacy, 32 meta‐analysis studies in bronchiolitis showed that HSS has a positive influence on both hospitalization rates and the length of stay 33,34 . In these cases, the action is mainly attributed to a decrease of the respiratory epithelium edema and work of breathing.…”
Section: Discussionmentioning
confidence: 99%